(untitled) (Revista Científica Compendium, 2020)
The theory of dynamic capabilities has been crucial to understanding innovation processes. Companies obtain superior performance and sustainable competitive advantages through such capabilities. Hence, the importance of the emergence of a theoretical and empirical scaffolding around the theory of dynamic capabilities. It seeks to explain the behavior of organizations in dynamic and changing environments. In this order of ideas, the present essay aims to raise some propositions in order to link dynamic capabilities with the innovation process. This, through the review and analysis of relevant literature on the subject. Finally, as a result, three main components of dynamic capabilities are considered: absorption capacity, adaptation capacity and learning capacity. These three dynamic capacities can have positive effects on the innovation capability of the company, thus becoming one of its enablers.